Pneumothorax in neonates: a level III Neonatal Intensive Care Unit experience - Íris Santos Silva; Filipa Flôr-; Gustavo Rocha; Inês Alves; Hercília Guimarães (Hygeia Press di Corridori Marinella, 2016)
Introduction: Pneumothorax occurs more frequently in the neonatal period than in any other period of life and is associated with increased mortality and morbidity. Several risk factors for pneumothorax, including respiratory pathology, invasive and non-invasive respiratory support, and predictors of mortality have been described. Objective: To evaluate the prevalence of pneumothorax, to assess risk factors and to describe the clinical characteristics, management and outcome of newborn infants with pneumothorax, as well as to identify predictors of mortality in these newborns. Methods: This retrospective case-control study included all newborns hospitalized in the Neonatal Intensive Care Unit (NICU) of "Centro Hospitalar São João", Porto, Portugal, between 2003 and 2014, with the diagnosis of pneumothorax. A control group was selected among the newborns without pneumothoraces, admitted to the same NICU during the same period. The collected data included: demographics and perinatal data, pneumothorax characteristics, classification, treatment and clinical outcomes. Results: Our study included 240 neonates (80 with pneumothoraces and 160 controls), of whom 145 were male (60.4%). Median gestational age was 37 (24-40) weeks and median birthweight 2,613 (360-4,324) grams. The prevalence in our NICU was 1.5%. Pneumothorax was significantly associated with respiratory distress syndrome (RDS) (p = 0.010) and transient tachypnea of the newborn (TTN) (p < 0.001). Invasive mechanical ventilation (MV) (p = 0.016) and FiO2 ≥ 0.4 (p = 0.003), were independent risk factors for the development of pneumothoraces. The mortality rate was 13.8%. Hypotension, MV and thoracentesis followed by a chest tube insertion were found to be predictors of mortality in newborns with pneumothoraces, but pneumothorax per se was not a predictor of mortality. Conclusion: Pneumothorax is relatively frequent in the NICU. Its risk factors and predictors of mortality should be known in order to prevent and treat this critical situation. Pneumothorax itself was not a predictor of mortality, probably due to the adequate and prompt management used in the NICU.